SU-F-J-21: Clinical evaluation of surface scanning systems in different treatment locations - Moser, Torsten; Stefanowicz, Sarah; Rhein, Bernhard; Oetzel, Dieter; Adeberg, Sebastian; König, Laila; Wolf, Robert; Rieken, Stefan; Karger, Christian (Medical physics, 2016)
Purpose: To reduce imaging dose in fractionated IGRT, the ability of optical surface imaging systems (OSIS) to detect setup errors was tested. Therefore, clinical studies to evaluate for different treatment locations setup corrections derived by OSIS in comparison with x-ray image guidance in fractionated radiation therapy was performed. Methods: The setup correction accuracy of an OSIS system (AlignRT, VisionRT, London, UK) will be analysed for the 4 tumour locations Pelvis, Upper Abdomen, Thorax and Breast, 20 patients for each location in comparison to a different system (Sentinel, C-RAD, SE). For each patient, the setup corrections of the cone-beam computed tomography (CBCT) of an Elekta Versa HD linear accelerator (Elekta, Crawley, UK) is considered as gold-standard and then compared with those of the OSIS for the first ten fractions retrospectively. There were no clinical decisions made based on the surrogate system. For the OSIS, the reference surface is highly important as it represents the actual ground truth. It can be obtained either with the system itself or the surface structure delineated in the planning CT can be imported via DICOM interface. In this paper, the first results for the treatment region thorax are presented. The reference image modalities were compared. Results: Table 1 displays the difference between the setup corrections obtained with OSIS and CBCT in lateral (LAT), longitudinal (LNG) and vertical (VRT) direction for the DICOM reference image. While the median deviations are within a few millimeters, some outliers showed large deviations. Generally, the mean deviation as well as the spread was smallest in lateral and largest in vertical direction. Conclusion: Although the system allows fast, simple and non-invasive determination of setup corrections, it should be evaluated treatment region dependant. Therefore, the study is ongoing. The application of OSIS may help to reduce the imaging dose for the patient. We gratefully acknowledge the support by our colleagues from the Radiological University Clinic Heidelberg, where the study was performed. This work was funded by the Federal Ministry of Education and Research (BMBF) Germany, grant number 01IB13001B.
Gesehen am 18.09.2020